Outcome of Medial Plating for Fracture Shaft of Humerus - Gupta, Hemant Kumar; Hamal, Rajkumar Ravi; Lamichhane, Suman (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Fracture shaft of humerus is commonly seen fracture which is managed by nonoperative and operative methods. Operative fixation allows early return to daily work with ease in rehabilitation and less complication. This study was conducted to evaluate outcome of fracture shaft of humerus treated with plating by anteromedial approach on medial surface of humerus. Methods A hospital based prospective study including 164 cases of humerus fracture shaft surgically managed with medial plating over a period 15th July 2017 to 14thJune 2022with the mean follow-up duration of 24 weeks was performed. The final outcome was evaluated on the basis of radiological union and Modified Stewart and Hundley Scoring criteria. Results Fracture united in 49.39% of cases within 12 weeks, 28.65% case united in 12-24 weeks time and 19.61% cases united later than 24 weeks. Non union seen in 4 cases in our study treated with bone grafting healed. Functional outcome was measured as per Modified Stewart and Hundley Scoringcriteria, it was excellent in 67.08% of cases, good in 18.29%, satisfactory in 7.93 % of cases. Poor results were seen in 6.7 percent of cases. Conclusions Anterolateral approach with medial plating was found to be better option for fixation of fracture shaft of humerus as per our study as it has fewer complication with comparable results to other literature.